SISTEM DETEKSI KEBAKARAN “SiDinKar” SECARA REAL TIME BERBASIS INTERNET OF THINGS - Chrisna Putra Buana; Dini Fakta Sari (KURVATEK, 2025)
The Fire Detection System emerged because of the many fires in the room. Aims for early detection of room / room conditions from the possibility of fires based Internet of Things. By utilizing internet connectivity in controlling hardware : smoke sensors, fire sensors and buzzer. Displays smoke and gas values and detects the presence or absence of fire in a room and provides notifications when the displayed value exceeds certain limits by using the mobile application on the Android smartphone and buzzer at NodeMCU. This tool uses several devices to connect the process between the response from the sensor and the application. Smoke sensors and fire sensors as data retrieval from objects. NodeMCU is used as a microcontroller. Firebase is used to store temporary data and to link applications with tools. The mobile application, namely SiDinkar, is used to monitor the conditions of gas, smoke and fire in the room. Notification in mobile application is used and buzzer in NodeMCU for alerts under certain conditions. The results of the tests that have been carried out are that the tool is able to display data in the form of smoke and fire taken from Firebase by the Android Application “SiDinKar”. The data displayed on the mobile application is realtime. To access the application in order to monitor realtime requires an internet connection.